ESTIMASI BIAYA PRODUKSI DALAM MERENCANAKAN LABA PADA PABRIK KARET PT. BUKIT ANGKASA MAKMUR KABUPATEN BENGKULU UTARA - Badrudin, Redy; Sugiarti, Sri; Marbun, Friska Oktora (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2006)
The aim of the factory is to get the profit. Large or small the advantage the profit that the factory can reached out, that’s provide the management ability/succesfull in manage their company. Into arrange the profit planning could done by analyzing Break Event Point (BEP) and the variananalysis to estimate the product cost, checking cost, and measurement of the factory performance.The purpose of this research is (1) To know is it the process of crumb rubber on Bukit Angkasa Makmur factory Ltd has reached the level of minimum sale? (2) To know how much the value number of margin contribution, and the ratio of margin contribution, (3) To know is it in production activity (production process) on PT. Bukit Angkasa Makmur get the favourable or unfavourable varian?, (4) To know the value number of fixed cost and variable cost on PT. Bukit Angkasa Makmur.The result of this research show that the PT. Bukit Angkasa Makmur has reached the minimum level of sale with Break Event Point value (in Rp) Rp 201.585.596.402,50 and 21.894.818,77 Kg. The value of margin contribution is Rp 8.339.796.662,00, and the ratio margin of contribution value is 0.04. The fixed cost on PT. Bukit Angksa Makmur in year of 2005 is Rp 8.063.423.856,10 with the variable cost Rp 221.881.029.070,92. The means of raw materials varianis Rp (36.507.552.431,99) favourable. The means of the direct employees is Rp (49.296,00) favourable. The means of overhead variable is Rp (175.905.700,76) favourable. The means of fixed averhead varianis Rp (118.626.927,28) favourable